Primary intravenous chemotherapy for group D retinoblastoma: a 13-year retrospective analysis. Issue 1 (13th December 2016) - Fabian, Ido D; Stacey, Andrew W; Johnson, Kenneth P; Onadim, Zerrin; Chowdhury, Tanzina; Duncan, Catriona; Reddy, M Ashwin; Sagoo, Mandeep S
Abstract : Background: Eye salvage rate for group D retinoblastoma using intravenous chemotherapy (IVC) as a primary modality is <50%. To report on 13 years' experience with the use of primary IVC for group D retinoblastoma. Methods: A retrospective analysis of 64 group D eyes (52 patients) treated with primary IVC, from 2002 to 2014. Results: The median age at presentation was 11.0 months (mean: 18.6, range: 0.6–144.0), 35 (67%) patients had bilateral disease, 38 (73%) germline disease and 8 (15%) cases were familial. In addition to IVC, patients received a median number of three treatments (mean: 6, range: 0–24), including thermotherapy/cryotherapy, plaque radiotherapy, intra-ophthalmic artery chemotherapy (IAC) and/or intravitreous chemotherapy. External beam radiotherapy (EBRT) was used in five eyes, all of which were eventually enucleated. In a median follow-up time of 55 months (mean: 64, range: 14–156), 63% of eyes were salvaged. By the Kaplan-Meier survival analysis, globe salvage rate was 83%, 70%, 59% and 45% at 1, 3, 5 and 10 years, respectively. There were no cases of metastatic spread from intraocular retinoblastoma and no deaths. IVC-related adverse events included febrile neutropenia in 21 (40%) patients and anaphylactic reaction to carboplatin in 2 (4%), all conservatively resolved. Of the patients receiving IAC, third and sixth nerve palsies were documented in two (10%) and one (5%) eyes, respectively. Conclusions: Primary IVC for group D eyes, with adjuvant treatments as required, was found to be a safe and efficient approach, achieving 63% eye salvage rate, no metastatic spread from intraocular retinoblastoma and no deaths. IAC has now replaced EBRT as a successful salvage treatment.